Respuesta :
[tex]c=14[/tex]
There is no extraneous solution because as we put the value of c in equation (1), it does not make the equation (1) not define.
Step-by-step explanation:
Given :
[tex]\dfrac {c-4}{c-2} = \dfrac {c-2}{c+2} - \dfrac{1}{2-c}[/tex] --------- (1)
Calculation :
[tex]\dfrac {c-4}{c-2} = \dfrac {(c-2)^2+(c+2)}{(c+2)(c-2)}[/tex]
[tex]c-4 = \dfrac {(c^2-4c+4)+(c+2)}{(c+2)}[/tex]
[tex](c-4)(c+2) = (c^2-3c+6)[/tex]
[tex](c^2-2c-8) = (c^2-3c+6)[/tex]
[tex]c=14[/tex]
There is no extraneous solution because as we put the value of c in equation (1), it does not make the equation (1) not define.
For more information, refer the link given below
https://brainly.com/question/11897796?referrer=searchResults